2005
DOI: 10.1111/j.1745-7254.2005.00528.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of P-glycoprotein function by amlodipine derivatives in brain microvessel endothelial cells of rats1

Abstract: Aim: To investigate whether the amlodipine derivatives, CJX1 and CJX2, have a modulative effect on P‐glycoprotein (P‐gp) function in rat brain microvessel endothelial cells (RBMEC). Methods: Isolated RBMEC were cultured in DMEM/F12 (1:1) medium. The amount of intracellular rhodamine (Rh123) was determined, using a fluorescence spectrophotometer, to evaluate the function of P‐gp. Results: The accumulation of Rh123 in RBMEC was potentiated in a concentration dependent manner after incubation with CJX1 and CJX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…The t 1/2 obtained here for rh123 efflux (~13 min) is in agreement with another study that found a t 1/2 of similar magnitude in rat primary BECs (~ 10 min) (Ji et al, 2005). However, in contrast to the relatively modest increase in the efflux t 1/2 caused by another competitive inhibitor, verapamil, in that study (t 1/2 ~ 20 min), in the present study vinblastine caused a much more potent inhibition (t 1/2 ~ 110 min).…”
Section: Accepted M Manuscriptsupporting
confidence: 80%
“…The t 1/2 obtained here for rh123 efflux (~13 min) is in agreement with another study that found a t 1/2 of similar magnitude in rat primary BECs (~ 10 min) (Ji et al, 2005). However, in contrast to the relatively modest increase in the efflux t 1/2 caused by another competitive inhibitor, verapamil, in that study (t 1/2 ~ 20 min), in the present study vinblastine caused a much more potent inhibition (t 1/2 ~ 110 min).…”
Section: Accepted M Manuscriptsupporting
confidence: 80%
“…Rhodamine 123 (Rh123) is a fluorescent dye that could be used as a function assay for P-gp [18,19]. Cells were seeded into 6- well plates at a density of 1 × 10 6 per well.…”
Section: Methodsmentioning
confidence: 99%
“…Similar results for CJZ3 have been observed in doxorubicinresistant human myelogenous leukemia (K562/DOX) cells (unpublished data). We also found that the ability of CJZ3 to cause the accumulation of Rh123 was greater than that of CJX1 and CJX2, the amlodipine derivatives studied previously [17] : the rate constant of uptake (K uptake ) was higher in 10 µmol/L CJZ3-treated cells (0.060) than in CJX1-treated cells (0.0508) and in CJX2-treated cells (0.0495), and the rate constant of efflux (K efflux ) was lower (0.0068) than in CJX1-treated cells (0.0097) and in CJX2-treated cells (0.0127), suggesting that CJZ3 also has a more potent inhibitory effect on P-gp function than CJX1 and CJX2.…”
Section: Discussionmentioning
confidence: 59%